2009
DOI: 10.1182/blood-2009-05-221606
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of NET formation by gene therapy in CGD controls aspergillosis

Abstract: IntroductionActivated neutrophils kill microbes intracellularly after phagocytosis and by extracellular mechanisms, including neutrophil extracellular traps (NETs), which are composed of chromatin decorated with granular proteins. 1 NETs bind bacteria 1 and fungi 2 and expose antimicrobial molecules. Generation of NETs requires reactive oxygen species produced by the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase. 3 Chronic granulomatous disease (CGD) is caused by mutations in genes encoding NADPH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
459
1
23

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 513 publications
(501 citation statements)
references
References 24 publications
18
459
1
23
Order By: Relevance
“…Furthermore, in a case of severe Aspergillosis in a CGD patient, negative correlation was found between the ability of neutrophils to form NETs and the severity of infection [10].…”
Section: Extracellular Killing By Neutrophilsmentioning
confidence: 95%
“…Furthermore, in a case of severe Aspergillosis in a CGD patient, negative correlation was found between the ability of neutrophils to form NETs and the severity of infection [10].…”
Section: Extracellular Killing By Neutrophilsmentioning
confidence: 95%
“…This in turn leads to a clinical picture of recurrent and/or persistent infections, in particular with fungal pathogens. Impressively, there has been a successful report of gene therapy, where an 8‐year‐old boy was treated with a retroviral vector containing a functional gp91 (PHOX subunit) gene, resulting in neutrophils regaining the ability to NETose and leading to a termination of an intractable Aspergillus nidans infection 51. Experimentally, inhibition of NADPHO or myeloperoxidase (MPO) effectively inhibited NETosis stimulated by PMA, whereas inhibition of mitochondrial respiration or superoxide dismutase did not 52.…”
Section: Histone Processing and Active Release During Netosismentioning
confidence: 99%
“…The results showed that NETs are formed during the early stages of infection. In addition to the reported induction of NETosis formation by bacteria [3,6,12,13], fungi [17][18][19] and protozoa [15], NETosis has also been shown to be induced by LPS-activated platelets [14] and by antineutrophil autoantibodies isolated from patients with SVV [16], whereas impaired degradation of NETs has been associated with systemic lupus erythematosus as well [20].…”
Section: Introductionmentioning
confidence: 99%